2020
DOI: 10.1001/jamanetworkopen.2020.4063
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pediatric Acute-Onset Neuropsychiatric Syndrome With Microstructural Differences in Brain Regions Detected via Diffusion-Weighted Magnetic Resonance Imaging

Abstract: IMPORTANCE Epidemiological studies indicate a link between obsessive-compulsive disorder and infections, particularly streptococcal pharyngitis. Pediatric acute-onset neuropsychiatric syndrome (PANS) manifests suddenly with obsessions, compulsions, and other behavioral disturbances, often after an infectious trigger. The current working model suggests a unifying inflammatory process involving the central nervous system, particularly the basal ganglia. OBJECTIVE To investigate whether diffusion-weighted magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 77 publications
1
33
0
Order By: Relevance
“…In particular, an enlarged striatal volume (Giedd et al, 2000;Elia et al, 2005) and an inflammatory state of the striatum, confirmed by positron emission tomography using a marker of microglial activation (Kumar et al, 2015), has been reported in PANDAS. A recent diffusion-weighted magnetic resonance imaging study identified cerebral microstructural differences in children with PANS in multiple brain structures (including deep gray matter structures such as the thalamus, basal ganglia, and amygdala) putatively related to a neuroinflammatory state (Zheng et al, 2020). In cohorts of rigorously selected subjects with PANS, evidence of post-infectious autoimmune processes and/or a condition of neuroinflammation was observed in over 80% of cases (Swedo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, an enlarged striatal volume (Giedd et al, 2000;Elia et al, 2005) and an inflammatory state of the striatum, confirmed by positron emission tomography using a marker of microglial activation (Kumar et al, 2015), has been reported in PANDAS. A recent diffusion-weighted magnetic resonance imaging study identified cerebral microstructural differences in children with PANS in multiple brain structures (including deep gray matter structures such as the thalamus, basal ganglia, and amygdala) putatively related to a neuroinflammatory state (Zheng et al, 2020). In cohorts of rigorously selected subjects with PANS, evidence of post-infectious autoimmune processes and/or a condition of neuroinflammation was observed in over 80% of cases (Swedo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroimaging studies indicate that microstructural differences (ie, apparent diffusion coefficient, but not regional brain volume nor cerebral blood flow) may be observed in the basal ganglia, thalamus, and amygdala of children and adolescents with PANS. 4 Interestingly, recent evidence indicates that also thalamus and amygdala play an important role in sleep regulation. 68 Considering the complex microstructure of the basal ganglia, 69 PANS neuro-inflammation may heterogeneously impact specific sub regions modulated by midbrain dopaminergic pathways, leading to apparently opposite symptoms (ie tics and PLMD).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, altered sleep has been linked to abnormalities in basal ganglia and neuroinflammatory diseases (ie, narcolepsy), and seeing that a recent study shows microstructural changes to the deep grey matter in patients with PANS, 4 it is not surprising that this PANS cohort has sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that PANS has an inflammatory or autoimmune etiology that is associated with an infection [11-15]. A recent MRI study in children with PANS showed an increased median diffusivity in multiple brain structures including basal ganglia, thalamus and amygdala compared to controls, suggesting neuroinflammation in these regions.…”
Section: Introductionmentioning
confidence: 99%